Searching for improved EFL classroom environments: the role of critical thinking-related tasks. (2003)
During the last decade, education in Colombia has gone through a series of continuos transformations whose ultimate purpose has been the search for academic quality and excellence. Such transformations have embraced the design, implementated new expectations regarding pedagogical practices.